Experimental Study: The Impact of Isometric Training on Increasing Muscle Capacity and Energy Efficiency in Soccer Athletes - Fatoni, Fatoni; Juhanis; Ihsan, Andi; Hamzah, Fajri; Mufarid, Andi Muhammad Rizky Al (Universitas Pendidikan Ganesha, 2025)
Abstract This study aims to examine the impact of isometric training on increasing muscle capacity and energy efficiency in soccer athletes. A total of 30 soccer athletes from the Faculty of Sport and Health Sciences, Universitas Negeri Makassar (UNM) were divided into two groups, namely the experimental group that underwent isometric training for 8 weeks and the control group that did not undergo the treatment. The isometric training program was carried out 3 times a week, with a duration of each training session of 30 minutes. The variables measured in this study included muscle strength, energy efficiency, oxygen use, and heart rate. Measurements were taken before and after the intervention in both groups to evaluate the differences that occurred. The results showed that the experimental group experienced a significant increase in muscle strength (from 75.4 ± 6.5 kg to 82.7 ± 5.4 kg) and energy efficiency (from 65.2 ± 4.3% to 70.8 ± 3.7%). In addition, there was a significant decrease in oxygen utilization (from 42.3 ± 3.1 ml/kg/min to 39.8 ± 2.8 ml/kg/min) and heart rate (from 138.5 ± 10.2 bpm to 132.4 ± 9.1 bpm). In contrast, the control group did not show significant changes in these variables. Based on these findings, it can be concluded that isometric training has a positive effect on increasing muscle strength and energy efficiency, as well as decreasing oxygen utilization and heart rate in soccer athletes.